Margret and H. A. Rey's Curious George and the dinosaur adapted from the Curious George film series - Rey, Margret 1906-1996 (Book & cassette favorites, 1989)
Curious George visits a museum with a class of schoolchildren and causes much excitement by climbing up onto a dinosaur skeleton